Cuban socialism and personality cult - Barrera Rivera, Abner (2020)
Since the triumph of the Cuban Revolution in 1959, its adversaries developeda large literary industry (articles, books and videos) with the aim ofattacking, assaulting and defaming it; among the accusations they made, wasthat in Cuba the cult of Fidel Castro's personality was promoted. The purposeof this article is to analyze if the cult of personality existed or exists in Cubansocialism. For that, it was resorted to some investigations made by journalists,historians and writers; also to the testimonies of different personalities,many of them foreign to politics and the Cuban Revolution, but who havebeen on the island, knowing it. The results of the article indicate that there isno evidence to sustain that Cuban socialism practiced or practices the cult ofpersonality; the government from the beginning not only did not allow it orpromote it, but it also prohibited it and fought against it. And that Fidel Castrohimself until the last days of his life, rejected that, even after his death,his name or his image was used for these purposes.